Theatrical Improvisation Short Form, Long Form, and Sketch-Based Improv - Leep, J. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
Theatrical Improvisation provides an in-depth analysis of short form, long form, and sketch-based improv - tracing the development of each form and the principles that define and connect the styles of performance. Brimming with original interviews from leaders in the field such as Ron West, Charna Halpern, John Sweeny and Margaret Edwartowski, Theatrical Improvisation presents straightforward improvisational theory, history, and trends. Includes easy-to-follow resources on teaching improvisation, with assessment tools, exercises, games, and classroom assignments to enable instructors to incorporate and assess improv in the classroom. Leep offers a practical, essential, and engaging guide for anyone who wants to better understand the art, teach, or perform improvisation.